Feeding colostrum with an esophageal feeder does not reduce immunoglobulin G absorption in neonatal dairy heifer calves - Elizondo Salazar, Jorge Alberto (2011)
Although the use of esophageal feeders is commonly recommended to aid in timely provision of colostrum to calves, there are few published studies that compare their effectiveness with other feeding methods. Therefore, newborn Holstein heifer calves (n = 40) were studied to compare total serum protein and IgG concentrations and apparent efficiency of absorption when colostrum was fed by nipple bottle or esophageal feeder. Calves were separated from their dams before suckling occurred, and a single feeding of 3.8 L of pooled colostrum was fed by 1.5 to 2 h of age using a nipple bottle, an esophageal feeder, or a combination of both. All calves received a total dose of 285 g of IgG. A jugular blood sample was collected from each calf at 0 and 24 h of age. No differences were detected (P > 0.05) between treatments in serum IgG concentration, total serum protein concentration, or apparent efficiency of absorption. Total serum protein averaged 6.4 ± 0.2 g/dL, total IgG was 24.4 ± 1.8 mg/mL, and apparent efficiency of absorption was 34.5 ± 2.9% (mean ± SEM).